Little Rock : race and resistance at Central High School - Anderson, Karen, 1947- (Politics and society in twentieth-century America., 2010)
The desegregation crisis in Little Rock is a landmark of American history: on September 4, 1957, after the Supreme Court struck down racial segregation in public schools, Arkansas Governor Orval Faubus called up the National Guard to surround Little Rock Central High School, preventing black students from going in. On September 25, 1957, nine black students, escorted by federal troops, gained entrance. With grace and depth, Little Rock provides fresh perspectives on the individuals, especially the activists and policymakers, involved in these dramatic events. Looking at a wide variety of evidence and sources, Karen Anderson examines American racial politics in relation to changes in youth culture, sexuality, gender relations, and economics, and she locates the conflicts of Little Rock within the larger political and historical context. --From publisher's description.